Anodization of sputtered substoichiometric aluminum oxide thin-films for improved nanorod array fabrication. (10th May 2017) - Patrovsky, Fabian; Fiehler, Vera; Derenko, Susan; Barth, Stephan; Bartzsch, Hagen; Ortstein, Katrin; Frach, Peter; Eng, Lukas M
Abstract: Optical sensing based on plasmonic nanorod arrays witnesses an increased interest for device applications due to a manifold of benefits of these structures, such as broadband optical tunability and low-cost bottom-up fabrication. Key to this success is the assembly of nanorod antenna arrays mediated through high-quality anodized aluminum oxide (AAO) matrices. The present work reports the greatly improved fabrication of thin-film AAO matrices based on aluminum thin-films deposited by magnetron sputtering under controlled argon/oxygen atmosphere, and investigates the influence of oxygen on the aluminum morphology and hence AAO pore formation upon anodization. Such optimized templates then subsequently allow the fast and reproducible fabrication of nanorod arrays with a nearly 100% pore-filling degree, which is favorable in plasmonic applications, with the plasmonic properties greatly benefiting from homogeneous distances between neighboring nanorods. For an optimal oxygen content of 10–22 at.%, we find the long-axis plasmon resonance peak to show the least optical losses, confirming the optimized nanostructure fabrication and performance.